Perlindungan Hukum terhadap Pembeli yang Beritikad Baik Atas Penjualan Objek Waris yang Belum Dibagi: Studi Kasus di Desa Pelawan Kabupaten Sarolangun - Putri, Regina Denita; Yuniawaty, Yenny (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Inheritance is a fundamental aspect of the Indonesian civil law system that regulates the transfer of rights and obligations from a deceased person to their heirs. According to Article 830 of the Indonesian Civil Code (KUH Perdata), inheritance can only occur upon death. In practice, problems often arise when one of the heirs sells the inherited property before the official distribution takes place. Such unilateral sale of an inheritance that is still considered part of the boedel waris (undivided estate) often leads to legal disputes, as it is carried out without the consent of all heirs and may cause losses to bona fide purchasers. The research method used is normative juridical, employing statutory and conceptual approaches. This study is descriptive-analytical in nature, aiming to examine the legal regulations concerning inheritance, sale and purchase agreements, and legal protection for bona fide buyers in the sale of undivided inheritance property. The data used consist of secondary data, including primary, secondary, and tertiary legal materials. The analysis is conducted qualitatively through legal interpretation of provisions in the Indonesian Civil Code (KUH Perdata), such as Articles 1320, 833, and 1365, to obtain a comprehensive understanding of legal protection for bona fide buyers. The research findings indicate that the sale of an undivided inheritance results in a legal consequence of being null and void, as the property remains part of the boedel waris (joint estate) collectively owned by all heirs. Conducting a sale without the consent of all heirs constitutes a violation of Article 1320 of the Indonesian Civil Code (KUH Perdata) concerning the validity requirements of an agreement, particularly regarding a specific object and a lawful cause. However, a bona fide purchaser is still entitled to legal protection under Article 1365 of the Civil Code, in the form of the right to claim reimbursement or compensation from the seller. Thus, such legal protection is compensatory in nature, aiming to maintain a balance between the heirs’ rights and the interests of third parties. It is therefore recommended that the division of inheritance be lawfully completed before any sale transaction takes place, and that prospective buyers verify whether the inheritance property has been properly divided or not.